2018
DOI: 10.3389/fncel.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Spike-Timing of Orbitofrontal Neurons Is Synchronized With Breathing

Abstract: The orbitofrontal cortex (OFC) has been implicated in a multiplicity of complex brain functions, including representations of expected outcome properties, post-decision confidence, momentary food-reward values, complex flavors and odors. As breathing rhythm has an influence on odor processing at primary olfactory areas, we tested the hypothesis that it may also influence neuronal activity in the OFC, a prefrontal area involved also in higher order processing of odors. We recorded spike timing of orbitofrontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 70 publications
(89 reference statements)
3
31
0
Order By: Relevance
“…Breathing and locomotion are also coupled oscillators. If and how distinct motor-related physiological variables influence cognitive cortical information processing during behavior remains to be further explored (Kőszeghy et al 2018;Ledberg and Robbe 2011;Lockmann et al 2016;Wyble et al 2004). The afferent and efferent connectivity of the medial septum suggests that it is at an important crossroad between sensory-motor and limbic pathways (Bland and Oddie 2001;Tsanov et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Breathing and locomotion are also coupled oscillators. If and how distinct motor-related physiological variables influence cognitive cortical information processing during behavior remains to be further explored (Kőszeghy et al 2018;Ledberg and Robbe 2011;Lockmann et al 2016;Wyble et al 2004). The afferent and efferent connectivity of the medial septum suggests that it is at an important crossroad between sensory-motor and limbic pathways (Bland and Oddie 2001;Tsanov et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the EEG alpha rhythm was shown to be modulated by the phase of the gastric cycle [7]. In a parallel line of work, we and others have recently described that nasal breathing rhythmically modulates neuronal activity in several brain regions [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 90%
“…Although the first reports of neuronal oscillations coupled to respiration date back to the seminal papers by Adrian [27,28], they were generally believed to occur in olfactory regions [but see 29]. However, a boom of papers published in the last 5 years convincingly demonstrated that rhythmic breathing also entrains non-olfactory networks [e.g., [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This locking or cortical respiratory potential (CRP) is lost after bulbectomy. CRP were also observed in the dorsal hippocampus of rats and mice, prominently in the dentate gyrus 28,29 , in medial and orbitofrontal prefrontal cortex (Pf) 19,30,31 , primary visual (V1) and primary motor (M1) cortex 32 . Other studies have showed that CRP also occurs in several regions of the human brain 33,34 .…”
Section: Introductionmentioning
confidence: 98%